Working overtime: The effects of overtime periods on game demands in basketball players - Scanlan, A. T.; Stanton, R.; Sargent, C.; O`Grady, C.; Lastella, M.; Fox, J. L. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To quantify and compare internal and external workloads in regular and overtime games and examine changes in relative workloads during overtime compared with other periods in overtime games in male basketball players. Methods: Starting players for a semiprofessional male basketball team were monitored during 2 overtime games and 2 regular games (nonovertime) with similar contextual factors. Internal (rating of perceived exertion and heart-rate variables) and external (PlayerLoad and inertial movement analysis variables) workloads were quantified across games. Separate linear mixed-models and effect-size analyses were used to quantify differences in variables between regular and overtime games and between game periods in overtime games. Results: Session rating-of-perceived-exertion workload (P=.002, effect size 2.36, very large), heart-rate workload (P=.12, 1.13, moderate), low-intensity change-of-direction events to the left (P=.19, 0.95, moderate), medium-intensity accelerations (P=.12, 1.01, moderate), and medium-intensity change-of-direction events to the left (P=.10, 1.06, moderate) were higher during overtime games than during regular games. Overtime periods also exhibited reductions in relative PlayerLoad (first quarter P=.03, -1.46, large), low-intensity accelerations (first quarter P=.01, -1.45, large; second quarter P=.15, -1.22, large), and medium-intensity accelerations (first quarter P=.09, -1.32, large) compared with earlier periods. Conclusions: Overtime games disproportionately elevate perceptual, physiological, and acceleration workloads compared with regular games in starting basketball players. Players also perform at lower external intensities during overtime periods than earlier quarters during basketball games.